ECOLOGICAL AND BIOLOGICAL CHARACTERISTICS OF BACTERIA OCCURRING IN THE RHIZOSPHERE OF PLANTS IN THE ARAL SEA REGION: https://doi.org/10.5281/zenodo.20483918 - Nematova, M.A.; Oripova, E.R.; Nurbekova, Z. (Scientific practical conference, 2026)
This article describes the diversity, ecological adaptability, and biological characteristics of rhizosphere bacteria associated with plants of the Aral Sea region. The rhizosphere is considered an important biological zone where microorganisms actively develop under the influence of organic compounds released by plant roots. Rhizosphere bacteria play a significant role in plant nutrition, mineral cycling, biological nitrogen fixation, phytohormone synthesis, and protection against phytopathogens. The extreme environmental conditions of the Aral Sea region, characterized by high salinity, drought, and ecological degradation, have contributed to the formation of halotolerant and salt-resistant microorganisms. Studies have revealed the widespread occurrence of bacterial genera such as Bacillus, Pseudomonas, Enterobacter, Arthrobacter, Rhodococcus, Micrococcus, and Streptomyces. These microorganisms are important biological resources for enhancing plant stress tolerance, restoring soil fertility, and supporting bioremediation and phytomelioration processes. Modern molecular-genetic methods, including 16S rRNA sequencing, metagenomics, and MALDI-TOF MS technologies, are increasingly used to investigate the functional and taxonomic diversity of the Aral Sea microbiome. The results demonstrate that rhizosphere microorganisms of the Aral Sea region represent a promising source for maintaining ecological stability and developing environmentally safe biopreparations.